Does the consolidated feed matter? - YU, Shihao (Institutional Knowledge at Singapore Management University, 2023)
In this paper we examine the role of the consolidated feeds in the current U.S. equities market by studying exogenous events which affect their speed and availability respectively. We find that faster consolidated feeds have an adverse, albeit mild, impact on market liquidity, possibly as a result of more non-high-frequency algorithmic trading activities from informed institutional traders. Moreover, when the consolidated feeds become corrupted or unavailable due to technical glitches, market liquidity significantly worsens. Our findings suggest that the consolidated feeds remain a crucial component of today’s market data infrastructure.